THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE, JOB SATISFACTION, AND WORK SPIRIT ON EMPLOYEE OF PERFORMANCE PT. ALFABIYA MITRA UTAMA BANJARMASIN - Saifullah, Ahmad; Agustina, Titien; Syamsuddinnor, Syamsuddinnor; Jatmika, Dodik (Penerbit Lafadz Jaya, 2024)
Employee performance is the core of human resource management. Employee performance is influenced by work motivation, work discipline, job satisfaction, and work spirit. Research into the influence of Work Motivation, Work Discipline, Job Satisfaction, and Work Spirit of PT Alfabiya Mitra Utama Banjarmasin employees needs to be carried out to determine their influence on employee performance. This research uses a quantitative approach with explanatory research. The research population consisted of 40 employees of PT Alfabiya Mitra Utama Banjarmasin. The sampling technique uses saturated or total samples. Data collection uses a questionnaire. The data analysis technique uses multiple linear regression analysis. The results of the research regression analysis show that the F table value in df 4 and df 32 in the F table is 0.12 with a significance of 0.000. The calculated F value reached 245.352. work motivation, work discipline, job satisfaction, and work spirit for the performance PT Alfabiya Mitra Utama Banjarmasin employees are simultaneously accepted because F count > F table and the significance is 0.000 <0.05. Work motivation influences employee performance because the significance is 0.019<0.05. Work discipline influences employee performance because the significance is 0.036<0.05. Job satisfaction influences employee performance because the significance is 0.033 <0.05. Job satisfaction influences performance because the significance is 0.000<0.05. Work motivation has a dominant influence on performance. So work motivation, work discipline, job satisfaction, and work spirit influence the performance of PT Alfabiya Mitra Utama Banjarmasin employees partially and simultaneously.